2007
DOI: 10.1029/2007gl030340
|View full text |Cite
|
Sign up to set email alerts
|

Decadal warming of the coldest Antarctic Bottom Water flow through the Vema Channel

Abstract: A decadal warming trend of Antarctic Bottom Water flowing through the Vema Channel is reanalyzed. Our data base consists of 94 high precision, full depth stations from 19 visits to the Vema Sill plus twelve stopovers at two additional key locations. Originally a long‐term temperature increase in the near‐bottom jet was noted from 1992 onward, after a period of rather constant abyssal temperatures since 1972. From today's perspective the apparent stagnant temperature level until 1991 can be interpreted as a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
55
1
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 16 publications
11
55
1
5
Order By: Relevance
“…The simulated dense shelf water cooling matches recent observational trends (Azaneu et al 2013) while preserving the observed warming of the densest waters within the Vema Channel (Zenk and Morozov 2007). No previous work provides a mechanism that may explain the observed cooling of dense shelf waters around Antarctica along with continued far-field warming.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The simulated dense shelf water cooling matches recent observational trends (Azaneu et al 2013) while preserving the observed warming of the densest waters within the Vema Channel (Zenk and Morozov 2007). No previous work provides a mechanism that may explain the observed cooling of dense shelf waters around Antarctica along with continued far-field warming.…”
Section: Discussionsupporting
confidence: 69%
“…Freshening of both shelf (waters shallower than 1000 m and south of 608S) and AABW water masses (Figs. 7d-f) is consistent with observational evidence (e.g., Zenk and Morozov 2007;Purkey and Johnson 2010;Hellmer et al 2012;Azaneu et al 2013). Freshening of shelf waters is greatest in the warming scenarios because of the dominant role ice removal has in the freshwater flux budget.…”
Section: B Shelf and Deep Ocean Responsesupporting
confidence: 76%
See 1 more Smart Citation
“…°C yr -1 from 1991 through to 2006, after being relatively stable from 1972 to 1991 (Zenk and Morozov, 2007). In the Brazil Basin, the abyssal layers warmed by ~0.04 °C between 1989(Johnson and Doney, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…A circulação abissal do Canal de Vemaé dominada pelaÁgua Antártica de Fundo (AAF; Antarctic Bottom Water, AABW A AAF, com temperaturas potenciais abaixo de 2 • C (correspondente a uma densidade ∼45,85 σ 4 ) nãoé uma massa d'água homogênea (Zenk & Morozov, 2007), podendo ser subdividida emÁgua Profunda do Mar de Weddell (APMW; Weddell Sea Deep Water, WSDW ), uma massa d'água mais densa encontrada junto ao fundo, eÁgua Circumpolar Inferior (ACI; Lower Circumpolar Deep Water, LCDW ) acima, sendo separadas pela isoterma de 0,2 • C. Logo acima, o fluxo dentro da camada ocupada pela APANé predominantemente dirigido para o sul com alguma influência da topografia. Hogg et al (1999) observaram que há um controle sobre a orientação e aceleração do fluxo sobre o Canal de Vema e a divisão do fluxo para oeste sobre uma depressão no Platô de São Paulo.…”
Section: Contexto Oceanográficounclassified